Determinants of Dividend Policy of Listed Commercial Banks in Indonesia - Gina Aulia; Mohamad Fany Alfarisi (AMAR (Andalas Management Review), 2019)
This study aims to identify the determinants of dividend payout policy of publicly listed banks in Indonesia. The data were collected from annual reports and databases related to the research sample. The present study employs the dynamic panel data model using the Generalized Methode of Moment (GMM) approach. The results without control variables suggest that lagged dividend payout, profitability, and firm size positively impact dividend payout. Meanwhile, using control variables, the present study finds only liquidity that significantly impacts the dividend payout.